Laparoscopic findings in patients with ectopic pregnancy diagnosis - Ávila Venegas, Carla (2015)
Objectives: To determine the most frequent findings in patients with diagnosis of ectopic pregnancy subjected to laparoscopic surgery. Design: Descriptive, retrospective, transversal study. Setting: Gynecology and Obstetrics Emergency Service, Hospital Alberto Sabogal Sologuren. Participants: Patients with ectopic pregnancy diagnosis treated by laparoscopy. Interventions: Twenty-six patients with diagnosis of ectopic pregnancy and considered suitable (hemodynamic stability and no contraindications for general anesthesia) were treated with laparoscopic surgery. We obtained information on age, hemodynamic status, ectopic pregnancy location, tumor size, presence of free fluid, type of surgery, conversion to laparotomy. Main outcome measures: Ectopic pregnancy characteristics and laparoscopy results. Results: Main age was 31,1 years. Isthmic and ampullar pregancies presented in the same proportion. Size of the tubal tumor was less than 5 cm in 23 (88,5%) patients. Salpingectomy was the most frequent surgical intervention, in 87,5%, and salpingostomy and adnexectomy were rarely performed. Laparoscopic conversion occurred in 7,7% of cases. Conclusions: Laparoscopy appeared as a safe method and good option for surgical treatment of ectopic pregnancy. An adequate evaluation of the patient is most important for surgery type decision. We did not find association between presence of hemoperitoneum over 100 mL and conversion to laparotomy.